Changes in Maternal Blood Inflammatory Markers As a Predictor Of Chorioamnionitis: A Prospective Multicenter Study. (29th September 2014) - Le Ray, Isabelle; Mace, Guillaume; Sediki, Mourad; Lirussi, Frédéric; Riethmuller, Didier; Lentz, Nathalie; Ramanah, Rajeev; Hoyek, Toufic; Spagnolo, Gilles; Laurent, Nicole; Goirand, Françoise; Sagot, Paul; et al.
<x xml:space="preserve">Abstract</x> Problem To evaluate the inflammatory pattern in maternal circulation from women with preterm premature rupture of membranes (PPROM) considering the occurrence of histologically confirmed chorioamnionitis (HCA). Method of study A prospective study was conducted in 121 women with PPROM between 24 and 34 + 0 weeks of gestation. Association between white blood cells (WBC) count, plasma CRP, IL‐6, MCP‐1 and IP‐10 levels, and HCA was assessed. Results The rate of HCA was 44.7% (54/121). During the 5 days preceding delivery, median CRP, WBC, and IL‐6 levels were significantly higher in the HCA than in no‐HCA group (P < 0.001). Variations in IL‐6, IP‐10 levels, during the 24–72 hr before delivery, were predictors of the occurrence of HCA, but the diagnostic accuracy was low [Receiver Operating Characterictic (ROC) curve, area under the curve (AUC) = 0.56]. Conclusion An increase in IL‐6, CRP, IP‐10 maternal plasma levels was confirmed in PPROM women with HCA. Longitudinal follow‐up of these markers did not add valuable information regarding HCA.